PERANAN SOSIALISASI NILAI KEBERSAMAAN DALAM UPAYA MENANGGULANGI KONFLIK BERAGAMA DALAM KEHIDUPAN BERMASYARAKAT DI KOTA PALANGKA RAYA - Erawati, Desi (IAIN Palopo, 2017)
Forum Kerukunan Antar Umat Beragama (FKUB) is a mediating institution on interfaith harmony, especially in the city of Palangkaraya. The question is how the value model of socialization of the value of togetherness conducted by FKUB Palangka Raya city so that it can bridge the life of tolerance between religious communities in the city of Palangka Raya. The methodology of this study is to use a research and development approach with a modified analysis of Miles and Huberman. The results of this study indicate that the working pattern of FKUB Palangka Raya works in accordance with the planned work program, proved to be able to handle several cases related to the establishment of houses of worship and its scope, prioritize the objectivity to produce mutually agreed decisions based on consensus reached agreement. The development of socialization of the value of togetherness is derived from several values such as the value of ideology (universal truth), religious values, cultural values. By way of coaching, intensive direction, then this togetherness attitude can be well established, especially supported by the value of local wisdom is the philosophy of